Environmental performance of biomethanation based on life cycle assessment - Patel, Gulam Husain; Horttanainen, Mika; Kokko, Marika; Yoruklu, Hulya Civelek; Havukainen, Jouni (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Climate change has recently had a significant impact on the environment, necessitating a shift from fossil-based to renewable energy sources. A promising long-term storage solution for renewable energy is the production of hydrogen through electrolysis, known as green hydrogen. This hydrogen can be utilized in Power-to-X applications, such as power-to-gas, where captured CO2 is used for methanation with hydrogen. Employing biomethane in place of natural gas in the transportation sector can significantly reduce greenhouse gas emissions. There is a research gap in the absence of comprehensive LCA studies comparing in-situ and ex-situ biomethanation processes with traditional biogas upgrading methods. The aim of the study is to evaluates the environmental performance of using hydrogen in in-situ and ex-situ biomethanation to increase methane content in biogas for heavy-duty vehicles, comparing these methods with traditional membrane separation upgrading. Through LCA, the climate change impact shows a 52 % reduction in emissions for membrane separation compared to fossil-based scenarios. Ex-situ biomethanation results in a 44%-54 % reduction, while in-situ biomethanation achieves 43%-53 %, depending on the electricity source for hydrogen production. Acidification and marine eutrophication impacts are higher in alternatives using grid electricity, while freshwater eutrophication stems from solar-powered hydrogen electrolysis. These findings underscore the importance of integrating renewable energy sources and advanced biogas upgrading techniques to achieve significant environmental benefits. The novelty of this research lies in its comprehensive LCA comparing traditional and innovative biogas upgrading technologies, providing valuable insights for future energy and environmental strategies.
Keywords: POWER-TO-GAS; ANAEROBIC-DIGESTION; ENERGY; SYSTEMS; TECHNOLOGY; MANAGEMENT; EMISSIONS; WASTE; LCA; Thermodynamics; Energy & Fuels